Fostering Value-Driven Leadership among Accounting Educators using the Qalb-Guided Framework - Tarmuji, Indarawati; Mahmud, Radziah; Tengku Embong, Tengku Fairuz (International Business Education Journal, 2024)
This research paper aims to comprehensively explore the significance of nurturing qalb-guided leadership attributes among accounting educators in Malaysia using qalb-guided framework. These educators play a pivotal role in moulding students into well-rounded individuals, embodying intellectual, spiritual, emotional, and physical balance while harmonizing with their families, communities, and country. The absence of qalb (heart) in leadership can lead to intellect devoid of emotion, resulting in negligence, lack of mindfulness, confusion, and uncertainty. In the contemporary landscape, the escalation of issues related to integrity, corruption, and unethical behaviour has become a pressing concern in both the realms of teaching and learning and the accounting profession, demanding immediate attention. Therefore, this paper elaborates on how the components of the qalb-guided leadership framework namely wisdom, justice, courage, and temperance can fortify the commitment, driving force, focus, energy, and synergy within accounting education across higher institutions. Simultaneously, it highlights the importance of fostering qalb attributes among accounting educators, challenges and strategies. This in-depth discussion is poised to contribute significant value to the existing literature on leadership quality issues. It is noteworthy that the integration of qalb-guided leadership elements in education is still in its early stages. Considering that the principles of wisdom, justice, courage, and temperance are universally applicable, underscoring its global relevance. Looking ahead, future research endeavours could involve empirical analysis using this approach once the qalb-guided leadership framework is established as a standard within higher education institutions. This strategic move would facilitate the exchange of knowledge and bolster any potential gaps in understanding.